A bioactive cartilage graft of IGF1-transduced adipose mesenchymal stem cells embedded in an alginate/bovine cartilage matrix tridimensional scaffold - Moncada Saucedo, Nidia Karina; Marino Martínez, Iván Alberto; Lara Arias, Jorge; Romero Díaz, Víktor J.; Camacho Morales, Alberto; Valdés Franco, José A.; Pérez Silos, Vanessa; García Ruíz, Alejandro; Lin, Hang; Tuan, Rocky S.; Ramos Payán, Rosalío; Lara Banda, María del Refugio; et al. (Hindawi Publishing Corporation, 2019)
Articular cartilage injuries remain as a therapeutic challenge due to the limited regeneration potential of this tissue. Cartilage engineering grafts combining chondrogenic cells, scaffold materials, and microenvironmental factors are emerging as promissory alternatives. The design of an adequate scaffold resembling the physicochemical features of natural cartilage and able to support chondrogenesis in the implants is a crucial topic to solve. This study reports the development of an implant constructed with IGF1-transduced adipose-derived mesenchymal stem cells (immunophenotypes: CD105+, CD90+, CD73+, CD14-, and CD34-) embedded in a scaffold composed of a mix of alginate/milled bovine decellularized knee material which was cultivated in vitro for 28 days (3CI). Histological analyses demonstrated the distribution into isogenous groups of chondrocytes surrounded by a de novo dense extracellular matrix with balanced proportions of collagens II and I and high amounts of sulfated proteoglycans which also evidenced adequate cell proliferation and differentiation. This graft also shoved mechanical properties resembling the natural knee cartilage. A modified Bern/O’Driscoll scale showed that the 3CI implants had a significantly higher score than the 2CI implants lacking cells transduced with IGF1 (16/18 vs. 14/18), representing high-quality engineering cartilage suitable for in vivo tests. This study suggests that this graft resembles several features of typical hyaline cartilage and will be promissory for preclinical studies for cartilage regeneration.